Fluorescent carbon nanodots for targeted in vitro cancer cell imaging - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Niryikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2016)
Carbon quantum dots (CQDs or C-dots, <= 10nm in size) are tiny carbon nanoparticles being envisaged in biosensing, bio-imaging and biomolecular/drug delivery. In the present investigation, green fluorescent carbon quantum/nano dots (GCQDs, similar to 3 nm in size) were synthesized through facile chemical slicing method. Further, folic acid (FA) functionalized GCQDs (GCQDs-FA) were obtained to enhance their targeting ability. FA is known to positively influence the binding potential and penetration into the cancer cells because of high abundance of folate receptors (FR) on various cancer cell membranes. We report high biocompatibility, photoluminescence stability and excellent in vitro cancer cell cytoplasm and nucleus targeting performance of GCQDs-FA on MCF-7 breast cancer cells. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cancer cell bio-imaging; Carbon quantum/nano dots; Cell cytoplasm and nucleus targeting; Green fluorescence; Photoluminescence stability; Targeting ability